Pengembangan Bahan Ajar Sistem Organ Tubuh Manusia Terintegrasi Komik dengan QR Code di Kelas V Sekolah Dasar - Nurul Ega Anggraini; Dyoty Auliya Vilda Ghasya; Muhammad Irfan Izudin (ALSYS, 2026)
Students’ limited understanding of the human organ systems indicates the need for teaching materials that meet the requirements of fifth-grade elementary school IPAS learning. This study aims to develop teaching materials on human organ systems integrating comics and QR codes, covering the human respiratory, digestive, and circulatory systems. This study employed the Research and Development method using the ADDIE model, limited to the analysis, design, and development stages. The teaching material product was validated by two content and language experts and two presentation and graphics experts. The research data were obtained through interviews to analyze the needs of fifth-grade teachers and students, while the data collection instruments included interview guidelines, validation questionnaires, and documentation. The findings show that the teaching materials obtained validity scores of 0.93 for the content aspect, 1.00 for the language aspect, 0.95 for the presentation aspect, and 0.91 for the graphics aspect, all of which were classified as highly valid. Based on these validation results, the teaching materials on human organ systems integrating comics and QR codes were declared suitable for use as a learning resource in fifth-grade elementary school IPAS learning. These findings indicate that the integration of comics and QR codes can produce teaching materials that meet content, language, presentation, and graphics feasibility standards and can be used as an alternative learning resource for human organ systems material.